Formability of Tailor-Welded Blanks from Dual-Phase and Bake-Hardened Steels with a Planar Anisotropy Influence - Schrek, A.; Švec, P; Brusilová, A. (Проблемы прочности, 2017)
The formability of two types of tailor-welded blanks was analyzed with the concentration on the effects of planar anisotropy on eras forming of deep-drawn parts. The first tailor-welded blank consisted of bake-hardened BH220 steel with different rolling directions, which is applied to the surface car body parts. The second one consisted of dual-phase DP600 steel with different rolling directions, which is applied to supporting parts of automobiles. Stress-strain characteristics of experimental steel sheets were measured using the tensile tests and used in the respective simulations. Simulations via the Dynaform software were compared to the experimental values measured during the deep-drawing process of rectangular boxes.